Perubahan tekanan darah dan heart rate recovery pasca olahraga aerobik mix impact (senam dayak) pada mahasiswa Universitas Palangka Raya - Steffany Angelina Monica; Balyas , Abi Bakring; Sitompul, Sanggap Indra; Toemon, Angeline Novia; Ahmad, Farah Fauziah Radhiyatulqalbi (Barigas: Jurnal Riset Mahasiswa, 2024)
One indicator of a person's heart health can be assessed by looking at resting heart rate (HR), resting blood pressure (BP), and cardiac output. Based on data from the Central Kalimantan Provincial Health Office, the prevalence of hypertension in 2019 was 34.47%. This figure shows that hypertension is still above the national average. This study aims to analyze changes in blood pressure and heart rate recovery after mix impact aerobic exercise in the form of dayak gymnastics in Palangka Raya University students. The research design used a descriptive research design using a cross-sectional study design. The subjects were 36 students of the Sendratasik Study Program who met the criteria. The instrument used was the Dayak gymnastics video. Data were analyzed using Univariate and Multivariate. Data analysis was carried out using the Friedman test, for BPs and TDd paired t-test, for heart rate recovery. The decrease in systolic and diastolic blood pressure after doing Dayak gymnastics occurred at minutes 30, 45, and significantly at minute 60 by 6.21/4 mmHg. While the decrease in heart rate recovery after Dayak gymnastics significantly occurred at minute 5 by 22.27 bpm